How Do Women React to the COVID-19 Pandemic Period? Relationship Between Ego-Resiliency, Anxiety, Alcohol Consumption and Aggression Among Polish Women - Florek S; Piegza M; Dębski P; Gorczyca P; Pudlo R (Dove Medical Press, 2023)
Szymon Florek,1,* Magdalena Piegza,2,* Paweł Dębski,2,3,* Piotr Gorczyca,2,* Robert Pudlo1,* 1Department of Psychoprophylaxis, Faculty of Medical Sciences in Zabrze, Medical University of Silesia, Katowice, Poland; 2Department of Psychiatry, Faculty of Medical Sciences in Zabrze, Medical University of Silesia, Katowice, Poland; 3Institute of Psychology, Faculty of Social Sciences and Humanities, Humanitas University in Sosnowiec, Sosnowiec, Poland*These authors contributed equally to this workCorrespondence: Szymon Florek, Email szymon.florek@sum.edu.plPurpose: There are many reports in the literature on the impact of the COVID-19 pandemic on mental health, including the condition of women. Most of these studies refer to a single time point, while there is a lack of studies controlling for selected parameters during different periods of the pandemic. This work aimed to determine the role of ego-resiliency in women's adaptation to the COVID-19 pandemic.Patients and Methods: The survey was conducted in two stages - all via online forms. A total of 762 Polish women took part in the overall project. The scales used in the study were the Ego-resiliency scale (ER89-R12), Generalized Anxiety Disorder 7 Scale (GAD-7), Alcohol Use Disorders Identification Test (AUDIT), and Buss-Perry Aggression Questionnaire (BPAQ). Statistical analysis was performed using Statistica 13.3.Results: Women participating in the second study had significantly lower scores on ego-resilience and its components compared to the first study. In the first research, ego-resiliency and optimal regulation were statistically significantly correlated with anxiety, alcohol consumption, generalised aggression, verbal aggression and hostility, while openness to life experiences was correlated with alcohol consumption and hostility. The second part of the project highlighted new significant correlations between ego-resiliency and optimal regulation and physical aggression and anger, but a non-significant correlation of these variables with alcohol consumption. The effect of openness to life experiences on alcohol consumption and anxiety, evident in the first study, was no longer present in the second part of the study.Conclusion: The lack of a significant effect of openness to life experience on alcohol consumption, lower ego-resiliency and optimal regulation scores are observed in the second part of the research, which might be an expression of adaptation to the COVID-19 pandemic. Ego-resiliency is a protective factor against aggression, while optimal regulation against anxiety among Polish women.Keywords: COVID-19, women, resiliency, adaptation, anxiety, aggression